Understanding social support during pregnancy: A qualitative study of women’s lived experiences in Nepal - Lalita Kumari Sah; Eleni Hatzidimitriadou; Rajeeb Kumar Sah (PLoS ONE, 2025)
This research study examines the experience and understanding of available social support in Nepal and its importance during pregnancy. The interviews, utilising twenty in-depth interviews with pregnant women in Nepal, were analysed inductively using a thematic analysis approach. The findings suggested that women consider their husband’s support the most important and desired support during pregnancy, while women also acknowledged support from relatives and neighbours. None of the women experienced any organised community support or NGO/INGO support, and the support from healthcare providers was limited. At the policy level, the maternity leave policy by the government of Nepal is seen as inadequate support in promoting working women in Nepal, and it lacks implementation in informal work sectors. The study concludes that appropriate social support can significantly enhance the well-being of pregnant women. Given the limited availability of formal support systems and the central role of spousal and informal community support, these findings highlight the need for context-specific interventions. Therefore, we recommend conducting interventional studies to design and evaluate targeted support mechanisms that address the diverse needs of pregnant women in Nepal, shaped by their socioeconomic and cultural contexts.